Removal of silicone oil following diabetic vitrectomy. Issue 4 (April 1993) - Pearson, R V; McLeod, D; Gregor, Z J
Abstract : The outcome of the removal of silicone oil from previously vitrectomised diabetic eyes was studied in a series of 25 eyes in 24 patients. Originally the patients presented with complex retinal detachments associated with proliferative diabetic retinopathy and all had reattached retinas after the initial operation. During the silicone tamponade, a number of complications had occurred. Cataract had developed in 14 eyes, glaucoma in eight, and reproliferation of fibrous membranes in 12. After the removal of silicone the retina redetached in three eyes (in all cases associated with severe postoperative haemorrhage), hypotony occurred in five eyes (transiently in four) and the seven eyes remaining phakic developed a cataract. In spite of these problems the eventual visual acuities returned to the immediate post-vitrectomy levels in almost all the eyes.